Preparation and characterization of poly (vinyl chloride) (PVC) based membrane for wastewater treatment. (April 2017) - Ghazanfari, Davoud; Bastani, Dariush; Mousavi, Seyyed Abbas
Abstract: This study concentrates on fabrication of low-cost antifouling membranes by incorporation of alumina in PVC membranes for membrane bioreactor (MBR). PVC based membranes were prepared via phase inversion method at different alumina contents. Pure water flux through the membranes and its antifouling properties in MBR setup at operating pressure of −0.4 bar were studied. The effects of the alumina on the morphology and physical properties of the membranes were investigated by scanning electron microscopy (SEM), atomic force microscopy (AFM), contact angle, pore size, viscosity, porosity, and mechanical properties. The results showed that the membrane with 3 wt% alumina exhibited excellent antifouling performance, lowest surface roughness, water permeability, and maximum pore size. The flux recovery increased from 69% to 86% when the alumina content increased from 0 wt% to 3 wt%. Most importantly the antifouling experiments revealed that the incorporation of alumina reduced membrane fouling, especially irreversible fouling. For higher alumina content (more than 3 wt%) contact angle and mechanical strength increased, but water permeation and flux recovery reduced.